Early Christian Epistolarity - Dulk, Matthijs den; Lieu, Judith M. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
Many surviving early Christian writings are in the form of letters, some sent by and to those named, others imagined. What did the authors, copyists, and later collectors intend by authoring or reworking letters , as opposed to other genres? How did the first or subsequent readers respond, differently perhaps than to a novel or history? In her Radboud Prestige Lectures in New Testament, published in this volume, Judith Lieu explores these questions by drawing on the concept of 'epistolarity.' Her lectures are followed by chapters by leading experts in the field who engage her work from different angles, finding points of contact and potential conversation between different texts and authors, together with possibilities for further exploration and application.